Perancangan Geographic Information System Berbasis Android Untuk Potensi Mebel Di Kecamatan Tahunan Kabupaten Jepara - Tamrin, Teguh; Zyen, Akhmad Khanif; Dina, Maula Hashina (Universitas Islam Negeri Walisongo Semarang, 2019)
Jepara is a city called carving city because it has a large furniture and carving industrypotential. Tahunan Subdistrict is an area located in Jepara regency with the biggest potential of the furniture industry compared to other districts. Everyone who wants to buy furniture from Tahunan may visit the showroom which is located not far from the main road because of the limited information about the potential of furniture, especially small and medium business category in less strategic locations. Judging from these problems, it is necessary to make an information system about the potential of furniture in Tahunan district based on android that is easy to use and integrated with Geographic Information System (GIS) to make itÂ easier for users to find directions to the location. The system development method used is Rapid Application Development (RAD) with Construct 2 as the maker of the application.